2019
DOI: 10.1155/2019/7898095
|View full text |Cite
|
Sign up to set email alerts
|

NPY Receptor 2 Mediates NPY Antidepressant Effect in the mPFC of LPS Rat by Suppressing NLRP3 Signaling Pathway

Abstract: Accumulated evidences show that neuroinflammation play a pivotal role in the pathogenesis of depression. Neuropeptide Y (NPY) and its receptors have been demonstrated to have anti-inflammative as well as antidepressant effects. In the present study, the ability of NPY to modulate depressive-like behaviors induced by lipopolysaccharides (LPS) in rats and the receptors and signaling mechanisms involved were investigated. Continuous injection LPS (i.p) for 4 days led to development of depressive-like behaviors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…NPY was down-regulated in depressed rats and up-regulation of NPY promoted learning and memory ability recovery in depressed rats. In the development of depressive-like behaviors, the rat models are manifested with reduced NPY expression [ 17 ]. Academically, the expression of NPY is evidenced to decline in mice with depression [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NPY was down-regulated in depressed rats and up-regulation of NPY promoted learning and memory ability recovery in depressed rats. In the development of depressive-like behaviors, the rat models are manifested with reduced NPY expression [ 17 ]. Academically, the expression of NPY is evidenced to decline in mice with depression [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…NPY is a hypothalamic orexigenic neuropeptide which is sufficient to prevent anxiety, social disorders and depressive symptoms [ 16 ]. Besides that, NPY and its receptors have been evidenced to impose anti-inflammatory and antidepressant effects on lipopolysaccharides-induced depression rat models [ 17 ]. Taken together, the combined interplay of HDAC1/miR-124-5p/NPY axis in depression is in ambiguity.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the results of the enzyme-linked immunosorbent assay showed that NPY and PYY 3–36 reversed the LPS-induced upregulation of IL-1β levels; this effect was also prevented by BIIE0246. These data suggest that NPY inhibits the NLRP3 pathway through Y2R to prevent neuroinflammation ( 87 ). In conclusion, the activation of Y1R and Y2R holds a particular inhibitory capacity in the secretion of pro-inflammatory factors.…”
Section: Npy Directly Regulates Immune Cellsmentioning
confidence: 96%
“…Nevertheless, Y5R antagonists also play an antidepressant role through the MAPK/ERK and PI3K signaling pathways ( 143 ). Besides, Y2R plays an antidepressant role by inhibiting the NLRP3 signaling pathway in LPS-induced depression model rats ( 87 ). Intriguingly, in turn, the depression-induced increase in NPY expression affects immune cell recruitment and cytokine secretion ( 18 ).…”
Section: Npy Indirectly Regulates the Immune Responsementioning
confidence: 99%
“…Neuropeptide Y, as well as its selective NPY Y2 receptor agonist (NPY13-36), is known to act as an endogenous anticonvulsant by modulating glutamatergic hippocampal excitability [25], while displaying inhibitory action on cytotoxic cellular edema, by regulating KCl-evoked glutamate release [52]. Interestingly, NPY is co-localized with SP on GABAergic interneurons and A1 neurons in supra-optic nuclei (despite different ATP-stimulated actions on vasopressin and oxytocine release) [53], among other organs [54], with some authors suggesting that NPY might counterbalance SP's action, namely on nociceptive pathways and/or inflammation [55,56].…”
Section: Discussionmentioning
confidence: 99%